“The Unexamined Life is not Worth Living”: Socratic Dialogue versus Sophist Debate at the Birth of Philosophy (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
The article is an analysis of the importance of Socrates in the history of philosophy, with special reference to his renowned dictum: “the unexamined life is not worth living”. The author argues that Socrates’ importance is the result of establishing Socratic dialogue as a manner of interaction, to be distinguished from debate.The differences between debate and dialogue are analysed at length. Whereas debates are engaged into in order to establish already fixed positions, and are only meant to bring opponents around to one’s own position, a dialogue starts with the docta ignorantia, displays a willingness to learn, follows the argument wherever it leads, and is prepared to progress to a position not shared by any dialogue partner initially. The author close-reads the passage in the Apologia from which the dictum in the title derives. He also discusses ways in which the statement has been appraised in the tradition of Western philosophy e.g. in the work of thinkers such as Gadamer and Popper.